Effects of Photoperiod Fragmentation on Lettuce Yield and Specific Energy Consumption in Indoor Farming Systems - Othman, Mohd Faiz; A. Wahid, Muhammad Ikhram; Batcha, Mohd Faizal Mohideen; Md Seri, Suzairin (International Journal of Integrated Engineering, 2026)
Energy efficiency remains a critical aspect for indoor farming, where electricity via artificial lighting dominates operational costs. Among the viable strategies for energy efficiency is photoperiod fragmentation. This study investigates the effects of four photoperiod configurations (continuous, intermittent, and segmented) on the yield and energy efficiency of Lactuca sativa (butterhead and green coral varieties). Experiments were carried on a 4-tier, multi-rack hydroponic system with wide-spectrum artificial lighting. An identical 14-hour daily photoperiod is provided, ensuring comparable light energy input, but varied the light/dark frequency (e.g., single 14h block vs. multiple short cycles). Results indicate that photoperiod structure significantly alters biomass accumulation and SEC, though outcomes are cultivar- and system-dependent. For butterhead lettuce, a segmented schedule (P3: 5h/4h/5h ON blocks) maximized rooted fresh mass (0.088 kg/plant) and minimized facility-level SEC to 52.2 kWh kg?¹, whereas highly frequent cycling (P4) resulted in a twofold increase in energy intensity (102.0 kWh kg?¹) due to severe yield penalties. Conversely, for green coral in a container system, the high-frequency schedule (P4) produced the highest yield and lowest lighting-only SEC (29.0 kWh kg?¹). These findings demonstrate that equal daily light duration does not guarantee comparable productivity. Furthermore, the study highlights the importance of energy boundaries; including HVAC loads significantly elevates SEC, confirming that non-lighting subsystems often define the ceiling for energy performance. Optimization of light/dark fragmentation offers a viable, zero-cost control strategy to enhance energy productivity in controlled environment agriculture.